An unexpected shift in constant year effects in female elite handball - Schorer, J.; Wattie, N.; Faber, I. R.; Büsch, D.; Baker, J. (Scandinavian Journal of Medicine & Science in Sports, 2024)
One of the most convincing studies about the importance of the cutoff date in relative age effects was when Helsen et al. (2000) showed that a shift in the date directly resulted in a change of birth month distributions in soccer. Over the past four decades, the role of the birth year has also been associated with relative age effects (as reflected in constant year effects). In this investigation, two studies attempted to replicate the shift of birth year distributions caused by a change in birth years in international female handball. In Study 1, the results from the female handball world championship 2017 showed a significant within-year effect overall and a constant year effect for players born 1988 and after. A second study was conducted with female players from world championships in 2009, 2011, 2013, and 2015. Results demonstrated small effect sizes for most tests. However, there was an unexpected trend toward a constant year effect shift at the age of 28 years. Several hypotheses are presented as an explanation for this trend.